Poland’s Energy Security in Light of a Statistical Analysis - Pach-Gurgul, Agnieszka (Comparative Economic Research. Central and Eastern Europe, 2013)
Energy security is a multi-faceted notion, being subject to evolution due to its changing character as an entity, a state, a process and a phenomenon. Discussion of the topic involves not only the question of energy security (treated both objectively and subjectively), but also the issue of its measurement, its main factors and determinants. The aim of this article is to attempt to formulate an answer to the following research questions: what is the energy security of a state and what is its nature? which indices can be used to define the energy security of a state? what is Poland’s energy security status in comparison with other European Union states in the light of statistical analysis? In the research on Poland’s energy security compared to the European Union, data clustering was carried out according to the following methods: the Ward method, the full bond (furthest neighbourhood) method, analysis using the k-means method, and multidimensional scaling. In order to define the shifts in the direction of Poland’s energy security, synthetic indices for 2000 and 2008 have been calculated. Obtaining the answers to the above questions allowed for defining the main trends in Poland’s activities aimed at increasing its energy security.